Clay mineral dating of displacement on the Sronlairig Fault: implications for Mesozoic and Cenozoic tectonic evolution in northern Scotland. (27th May 2019) - Kemp, Simon J.; Gillespie, Martin R.; Leslie, Graham A.; Zwingmann, Horst; Campbell, S. Diarmad G.
Abstract: Temporary excavations during the construction of the Glendoe Hydro Scheme above Loch Ness in the Highlands of Scotland exposed a clay-rich fault gouge in Dalradian Supergroup psammite. The gouge coincides with the mapped trace of the subvertical Sronlairig Fault, a feature related in part to the Great Glen and Ericht–Laidon faults, which had been interpreted to result from brittle deformation during the Caledonian orogeny ( c. 420–390 Ma). Exposure of this mica-rich gouge represented an exceptional opportunity to constrain the timing of the gouge-producing movement on the Sronlairig Fault using isotopic analysis to date the growth of authigenic (essentially synkinematic) clay mineralization. A series of fine-size separates was isolated prior to K–Ar analysis. Novel, capillary-encapsulated X-ray diffraction analysis was employed to ensure nearly perfect, random orientation and to facilitate the identification and quantification of mica polytypes. Coarser size fractions are composed of greater proportions of the 2 M 1 illite polytype. Finer size fractions show increasing proportions of the 1 M illite polytype, with no evidence of 2 M 1 illite in the finest fractions. A series of Illite Age Analysis plots produced excellent R 2 values with calculated mean ages of 296 ± 7 Ma (Late Carboniferous–Early Permian) for the oldest (2 M 1 ) illite and 145 ± 7 Ma (Late Jurassic–Early Cretaceous) for the youngest (1 M ) illite. The Late Carboniferous–Early Permian (Faulting event 1) age may represent resetting of earlier-formed micas or authigenesis during dextral displacement of the Great Glen Fault Zone (GGFZ). Contemporaneous WNW(NW)–ESE(SE) extension was important for basin development and hydrocarbon migration in the Pentland Firth and Moray Firth regions. The Late Jurassic–Early Cretaceous (Faulting event 2) age corresponds with Moray Firth Basin development and indicates that the GGFZ and related structures may have acted to partition the active extension in the Moray Firth region from relative inactivity in the Pentland Firth area at this time. These new age dates demonstrate the long-lived geological activity on the GGFZ, particularly so in post-Caledonian times where other isotopic evidence for younger tectonic overprints is lacking.